2003
DOI: 10.1046/j.1365-2648.2003.02707.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and nurses’ experiences of perioperative dialogues

Abstract: If perioperative nurses used the perioperative dialogue they could create continuity for patients and for themselves in the pre-, intra- and postoperative phases. The nurse is, in this context, the continuity and continuity gives the possibility of establishing a caring relationship and caring for the patient in a dignified way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 20 publications
2
70
0
7
Order By: Relevance
“…This approach is the contrary to humanism and normative ethics, as these two aspects imply an understanding of the connection between the patient's vulnerability and the actions of the professional [14,17]. Establishing and maintaining the nurse-patient interaction can give NAs a sense of meaning in their work and help the patient to become more prepared for various nursing interventions [20].…”
Section: Reflection On the Resultsmentioning
confidence: 99%
“…This approach is the contrary to humanism and normative ethics, as these two aspects imply an understanding of the connection between the patient's vulnerability and the actions of the professional [14,17]. Establishing and maintaining the nurse-patient interaction can give NAs a sense of meaning in their work and help the patient to become more prepared for various nursing interventions [20].…”
Section: Reflection On the Resultsmentioning
confidence: 99%
“…Una de las habilidades es el cuidado individualizado encaminado a conocer las necesidades, experiencias, comportamientos y percepciones del paciente; a reconocer su unicidad y la de su familia (37,38,39,40,41,42), y una responsabilidad con la calidad de su práctica por las acciones que llevan a cabo, las que delega y por el mantenimiento de los estándares de la práctica de enfermería (43).…”
Section: Resultsunclassified
“…Pain inflicted by healthcare professionals might provoke anxiety, and in our unconscious mind, pain might be linked to threat and danger [36]. Research on patients' experiences of dialogues prior to, during and after surgery with the same nurse, however, revealed that patients considered the talks they had and the continuity to be anxiety-reducing [37] [38] and even that they "prevented and alleviated suffering in surgical procedures" [37]. This idea is supported in a study about children's healthcare.…”
Section: Discussionmentioning
confidence: 99%